Peran Inkubator Terhadap Pengelolaan Keuangan Startup Untuk Memperoleh Pendanaan - Raihan Putra Haristianto; Rifqi Muhammad (Jurnal Akuntan Publik, 2023)
Incubators are organizations that support and guide new entrepreneurs in developing their businesses. Incubators can help new entrepreneurs develop products, create strategic business, marketing, operational management and financing. Financial management is a measure of the performance of a business which is characterized by good financial records. New entrepreneurs need to have skills or knowledge of financial management which is a vital part of the company. Startup companies in Indonesia are always innovating in providing solutions to problems that occur in Indonesia. Funding is important for startups so they can develop their business, expand their market, and improve their products. Proper funding will help startup businesses expand and achieve their goals. The research method that the writer uses is descriptive qualitative research. The role of the incubator for startup financial management to obtain funding is to provide assistance and assist startups in drafting budgets, achieving profit targets, and preparing financial reports..